2019
DOI: 10.2174/1385272823666190314153208
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles: An Efficient Nano-catalyst

Abstract: Magnetic iron oxide nanoparticles have attracted attention because of their idiosyncratic physicochemical characteristics and vast range of applications such as protein separations, catalysis, magnetic resonance imaging (MRI), magnetic sensors, drug delivery, and magnetic refrigeration. The activity of the catalyst depends on the chemical composition, particle size, morphology and also on the atomic arrangements at the surface. The catalytic properties of iron oxide nanoparticles can be easily altered by contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 116 publications
1
12
0
Order By: Relevance
“…As already illustrated in some of the examples provided above, metal-oxide NPs have on occasion been used for organic conversions. 1908,1913 In one example, the promotion of the carbamoylation of aromatic amines was determined to be the most favored with CeO 2 NPs with nanooctahedra shapes (which expose [111] surfaces), followed by nanorods (with their [110] facets) and then nanocubes (and their [100] exposed faces); the trend was explained using results from quantum mechanics calculations as due to a combination of effects on the energetics of the individual elementary steps of the reaction (Figure 134). 1914 Another example involves the use of Cu 2 O NPs for the reduction of 4-nitropheno to 4aminophenol: it was concluded that the [111] facets are the most active for this reaction.…”
Section: Metal-oxide Clusters and Nanoparticlesmentioning
confidence: 99%
“…As already illustrated in some of the examples provided above, metal-oxide NPs have on occasion been used for organic conversions. 1908,1913 In one example, the promotion of the carbamoylation of aromatic amines was determined to be the most favored with CeO 2 NPs with nanooctahedra shapes (which expose [111] surfaces), followed by nanorods (with their [110] facets) and then nanocubes (and their [100] exposed faces); the trend was explained using results from quantum mechanics calculations as due to a combination of effects on the energetics of the individual elementary steps of the reaction (Figure 134). 1914 Another example involves the use of Cu 2 O NPs for the reduction of 4-nitropheno to 4aminophenol: it was concluded that the [111] facets are the most active for this reaction.…”
Section: Metal-oxide Clusters and Nanoparticlesmentioning
confidence: 99%
“…As hard, they have been used in magnetic recording media, while as soft, they have been used in magnetic recording heads, inductors, electromagnets, transformer cores, and other components of electrical devices. Iron oxide particles have been used for the very same applications as metallic iron, including environmental remediation and pollution detection, catalysis of organic reactions, and magnetic data storage . However, compared to metallic iron, iron oxide particles, mostly because of their greater stability, have found broader uses, which include the use as a coloring agent, a gas sensing material, an impurity control agent, a magnetic refrigeration agent, a contrast agent in magnetic resonance imaging (MRI), a drug delivery carrier, a cell and antibody identification and separation agent, a magnetic hyperthermia agent, and so on. Silica particles have been used in a number of optoelectronic applications, but also in oil–water separation and water purification technologies .…”
Section: Monophasic Compositionsmentioning
confidence: 99%
“…Indeed, the synthesis and use of iron nanoparticles in catalysis has led to an increased interest in recent years with the development of protocols leading to crystalline iron NPs with different shapes and sizes. [13][14][15] In this context, we report here the preparation of very small zero-valent iron nanoparticles (1-2 nm) following a very simple protocol avoiding the use of surfactants or classical stabilizing agents (such as phosphine or amine) as well as that of high temperature boiling solvent (such as oleic acid or polyols) classically reported in the literature. Such iron NPs resulted very different from those described in the literature: they are remarkably small, non-metallic and non-crystalline as described hereafter, where their properties are analyzed in detail and related to their physico-chemical and structural features.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, iron NPs were targeted. Indeed, the synthesis and use of iron nanoparticles in catalysis has led to an increased interest in recent years with the development of protocols leading to crystalline iron NPs with different shapes and sizes [13–15] . In this context, we report here the preparation of very small zero‐valent iron nanoparticles (1–2 nm) following a very simple protocol avoiding the use of surfactants or classical stabilizing agents (such as phosphine or amine) as well as that of high temperature boiling solvent (such as oleic acid or polyols) classically reported in the literature.…”
Section: Introductionmentioning
confidence: 99%